JANDA DAN DUDA: GENEALOGI PENGETAHUAN DAN KULTUR MASYARAKAT TENTANG JANDA SEBAGAI PELANGGENGAN KUASA PATRIARKI - M. Ali Sofyan; Syamsul Bakhri; Chinedu C Agbo (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Marital status is a cultural benchmark in assuming that a person is an adult. Similarly, Janda or Duda. For Janda, the community still considers one eye when compared to Duda. Events that cause a Janda for the community (village, especially) will usually be seen by women as the guilty party. Furthermore, when the status of the Janda is officially assumed, the community will observe its activities. For example, coming home late, not working, not socializing, or anything else. The discussion will be drawn to the discourse of the body and mind of a Janda has been executed and controlled by the mind in a patriarchal culture. This condition does not occur in Duda. For any Duda, the community considers it normal. In the divorce process widowers tend not to be seen as guilty parties. This research is a qualitative study with a phenomenological method in Central Java and Yogyakarta. The results of this study indicate that from the beginning until today the condition of women (Janda) has not changed much, The rights attached to Janda are reproduced by the public which gave rise to marginalization and stereotypes; The social space for Janda has shifted to the imbalance of power relations; myths and symbolic violence experienced by Janda because culturally the behavior of Janda is a public concern; Symbolic violence is experienced by Janda due to negative assumptions about their activities; patriarchal power always shackles women into a space of injustice; A public dominated by patriarchal culture eventually forms an unequal power discourse.